2021
DOI: 10.1038/s41586-021-03500-8
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic and epigenomic cell atlas of the mouse primary motor cortex

Abstract: Single-cell transcriptomics can provide quantitative molecular signatures for large, unbiased samples of the diverse cell types in the brain1–3. With the proliferation of multi-omics datasets, a major challenge is to validate and integrate results into a biological understanding of cell-type organization. Here we generated transcriptomes and epigenomes from more than 500,000 individual cells in the mouse primary motor cortex, a structure that has an evolutionarily conserved role in locomotion. We developed com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
259
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 234 publications
(290 citation statements)
references
References 69 publications
9
259
0
Order By: Relevance
“…3b). We co-clustered L5 ET cells from the Epi-retro-seq data and the snRNA-seq 10x v3 B data 37 , and found that the consensus transcriptomic cluster L5 ET_1 corresponded to Epi-retro-seq clusters 0, 2 and 3, whereas transcriptomic clusters L5 ET_2-4 corresponded to Epi-retro-seq clusters 1, 4 and 5, which contain almost no MY-projecting neurons (Fig. 8d).…”
Section: Articlementioning
confidence: 97%
See 4 more Smart Citations
“…3b). We co-clustered L5 ET cells from the Epi-retro-seq data and the snRNA-seq 10x v3 B data 37 , and found that the consensus transcriptomic cluster L5 ET_1 corresponded to Epi-retro-seq clusters 0, 2 and 3, whereas transcriptomic clusters L5 ET_2-4 corresponded to Epi-retro-seq clusters 1, 4 and 5, which contain almost no MY-projecting neurons (Fig. 8d).…”
Section: Articlementioning
confidence: 97%
“…We describe a synthesis of eleven companion studies through a coordinated multi-laboratory effort. In these studies, we derive a cross-species consensus molecular taxonomy of cell types using scRNA-seq or single-nucleus RNA sequencing (snRNA-seq), DNA methylation and chromatin accessibility data [37][38][39][40] . In mouse, we map the spatial cellular organization by multiplexed error-robust fluorescence in situ hybridization (MERFISH) 41 , characterize morphological and electrophysiological properties by multimodal profiling using patch clamp recording, biocytin staining and scRNA-seq (Patch-seq) 42,43 , describe the cellular input-output wiring diagrams by anterograde and retrograde tracing 44 , identify glutamatergic neuron axon projection patterns by Epi-retro-seq 45 , Retro-MERFISH 41 and single-neuron complete morphology reconstruction 46 , and describe transgenic driver lines targeting glutamatergic cell types on the basis of marker genes and lineages 47 .…”
Section: Articlementioning
confidence: 99%
See 3 more Smart Citations